Conflicto, salud y satisfacción: diferencias por etapa en parejas de la Ciudad de México - Flórez Rodríguez, Yanitza Nicole (2022)
The relationships go through different situations that can generate instability and upsets or conflicts between the members of the couple, which impact on it, favoring dissatisfaction, frustration or even the end of the relationship, greatly affecting the health and well-being of the person. Based on this, the objective of this study was to know the relationship among the conflict reasons and importance with health and satisfaction with the relationship. To this end, we worked with 240 people (50% women and 50% men), aged between 18 and 75 years who were in one of the four stages of the couple’s cycle: development, maintenance with small children, maintenance with older children and dissolution.